Proceedings of the 4th International Conference on Applications in Nonlinear Dynamics (ICAND 2016) - In, Visarath; Longhini, Patrick; Palacios, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents collaborative research works carried out by experimentalists and theorists around the world in the field of nonlinear dynamical systems. It provides a forum for applications of nonlinear systems while solving practical problems in science and engineering. Topics include: Applied Nonlinear Optics, Sensor, Radar & Communication Signal Processing, Nano Devices, Nonlinear Biomedical Applications, Circuits & Systems, Coupled Nonlinear Oscillator, Precision Timing Devices, Networks, and other contemporary topics in the general field of Nonlinear Science. This book provides a comprehensive report of the various research projects presented at the International Conference on Applications in Nonlinear Dynamics (ICAND 2016) held in Denver, Colorado, 2016. It can be a valuable tool for scientists and engineering interested in connecting ideas and methods in nonlinear dynamics with actual design, fabrication and implementation of engineering applications or devices.
From the Content: Invariant Tori in a Network of Two Spin-Torque Nano Oscillators -- Random Perturbations of a Three-machine Power System Network -- A Solvable Chaotic Oscillator with Multiple Set Points. .
Keywords: Dynamics; Nonlinear theories; Nonlinear Optics; Applied Dynamical Systems; Nonlinear Optics